High Capacity Functionalized Protein Superabsorbents from an Agricultural Co‐Product: A Cradle‐to‐Cradle Approach. (14th July 2020) - Capezza, Antonio Jose; Cui, Yuxiao; Numata, Keiji; Lundman, Malin; Newson, William Roy; Olsson, Richard Tobias; Johansson, Eva; Hedenqvist, Mikael Stefan
Abstract: Synthesis of superabsorbent particles from nontoxic wheat gluten (WG) protein, as an industrial co‐product, is presented. A natural molecular cross‐linker named genipin (a hydrogenated glycoside) is used together with a dianhydride (ethylenediaminetetraacetic EDTAD), to enable the preparation of a material with a network structure capable of swelling up to ≈4000% in water and ≈600% in saline solution. This represents an increase in swelling by over 10 times compared to the already highly absorbing gluten reference material. The carboxylation (using EDTAD) and the cross‐linking of the protein result in a hydrogel with liquid retention capacity as high as 80% of the absorbed water remaining in the WG network on extensive centrifugation, which is higher than that of commercial fossil‐based superabsorbents. The results also show that more polar forms of the reacted genipin are more effectively grafted onto the protein, contributing to the swelling and liquid retention. Microscopy of the materials reveals extensive nanoporosity (300 nm), contributing to rapid capillarity‐driven absorption. The use of proteins from agricultural industries for the fabrication of sustainable protein superabsorbents is herein described as an emerging avenue for the development of the next generation daily‐care products with a minimal environmental impact. Abstract : Protein‐based superabsorbents may be a way forward in the fight against climate change and microplastics. A cradle‐to‐cradle‐inspired approach for materials with minimal environmental impact, using an available and biodegradable agricultural co‐product as an alternative for current petroleum‐based superabsorbents is presented. Wheat gluten is here treated with nontoxic reagents, providing high water, saline, and blood uptake with a high liquid holding properties.